Mapping DNA structural variation in dogs - Chen, Wei-Kang; Swartz, Joshua D.; Rush, Laura J.; Alvarez, Carlos E. (Genome Research, 2009)
DNA structural variation (SV) comprises a major portion of genetic diversity, but its biological impact is unclear. We propose that the genetic history and extraordinary phenotypic variation of dogs make them an ideal mammal in which to study the effects of SV on biology and disease. The hundreds of existing dog breeds were created by selection of extreme morphological and behavioral traits. And along with those traits, each breed carries increased risk for different diseases. We used array CGH to create the first map of DNA copy number variation (CNV) or SV in dogs. The extent of this variation, and some of the gene classes affected, are similar to those of mice and humans. Most canine CNVs affect genes, including disease and candidate disease genes, and are thus likely to be functional. We identified many CNVs that may be breed or breed class specific. Cluster analysis of CNV regions showed that dog breeds tend to group according to breed classes. Our combined findings suggest many CNVs are (1) in linkage disequilibrium with flanking sequence, and (2) associated with breed-specific traits. We discuss how a catalog of structural variation in dogs will accelerate the identification of the genetic basis of canine traits and diseases, beginning with the use of whole genome association and candidate-CNV/gene approaches.
10.1101/gr.083741.108